(untitled) (Biological Sciences - PJSIR, 2004)
18:1 Colletotrichum lindemuthianum, the causative agent of anthracnose in beans (Phaseolus vulgaris) was successfully cul- tured in a complex medium of glucose/neopeptone. The extracellular High Molecular Weight Culture Filtrate Elicitor (HMWCFE) was isolated by simultaneous dialysis and ultrafiltration of nominal cutoff 30,000 dalton cartridge systems. Chromatographic separation provided two fractions Partially Purified Fraction, PPF-I (Mr 2000,000) and PPF-II (Mr < 40,000). Extraction with organic solvents showed that lipid was found in crude preparations. Methanolysis of PPF-I and II analyzed by GC, provided a series of fatty acids characterized by GC-MS viz: behenic (C22), arachidic (C20), isostearic (C18), oleic (C9 ), palmitic (C16), myristic (C14) and capric (C10) acids. Not all the lipid material was released under mild basic hydrolyzing conditions indicating the presence of some stable linkages between lipid and sugar moieties.